2005
DOI: 10.1007/s10682-005-8310-6
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Pre- and Post-Insemination Sexual Selection on Extreme Variation in Male Body Size

Abstract: Orb-weaving spiders of the genus Nephila are notable for their sexual size dimorphism, with dwarf males and giant females. However, less well known is the extreme size polymorphism of males that is characteristic of some species. For example, adult male body size in N. edulis varies by an order of magnitude. Previous experiments reveal that male mating behaviour covaries with body size, suggesting the size variation is maintained by opposing pre-and post-insemination sexual selection pressures. Here, we test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 37 publications
(57 reference statements)
1
31
1
2
Order By: Relevance
“…Further, experimental studies in which both preand post-insemination selection pressures can act together over a longer time revealed no comparative advantage for small or large males (Schneider and Elgar, 2005;Elgar and Jones, 2008). Finally, only one of two studies that investigated mate search revealed a large size advantage, and studies of two species indicated that large males were more likely to avoid sexual cannibalism.…”
Section: Experimental Evidencementioning
confidence: 95%
See 2 more Smart Citations
“…Further, experimental studies in which both preand post-insemination selection pressures can act together over a longer time revealed no comparative advantage for small or large males (Schneider and Elgar, 2005;Elgar and Jones, 2008). Finally, only one of two studies that investigated mate search revealed a large size advantage, and studies of two species indicated that large males were more likely to avoid sexual cannibalism.…”
Section: Experimental Evidencementioning
confidence: 95%
“…Perhaps these experimental results are evolutionarily trivial because they focus on single components of selection that have little impact on macro-evolutionary processes. Indeed, experiments that combined pre-and post-insemination selection pressures revealed no relationship between male size and paternity share (Schneider and Elgar, 2005;Elgar and Jones, 2008).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, males of N. plumipes cannot improve their paternity success by repeatedly mating with the same female, unlike males of the congenor N. edulis (Schneider et al 2000;Schneider and Elgar 2005;Elgar and Jones 2008;Jones and Elgar 2008), despite the possible increase in paternity share (see Elgar et al 2003b). Sexual cannibalism per se does not provide a greater paternity share or strongly reduce female receptivity (Elgar et al 2003b).…”
Section: Discussionmentioning
confidence: 99%
“…Non-adaptive developmental responses to dietary stress have been demonstrated experimentally in N. clavipes juveniles, which both over-eat (Higgins and Rankin 2001) and fail to reach maturity on low diets (Higgins and Goodnight 2010). There is also strong evidence of size-linked reproductive strategies (Christenson et al 1985) that, in male N. edulis, produce equivalent reproductive success (Schneider and Elgar 2005). The behavioral ''compensation'' for maturation at different sizes may contribute to the extreme degree of variation in size in males of this species (Schneider and Elgar 2005).…”
Section: Introductionmentioning
confidence: 99%